2010
DOI: 10.1038/hdy.2010.72
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding depression and low between-population heterosis in recently diverged experimental populations of a selfing species

Abstract: In fragmented populations, genetic drift and selection reduce genetic diversity, which in turn results in a loss of fitness or in a loss of evolvability. Genetic rescue, that is, controlled input of diversity from distant populations, may restore evolutionary potential, whereas outbreeding depression might counteract the positive effect of this strategy. We carried out self-pollination and crosses within and between populations in an experimental subdivided population of a selfing species, Triticum aestivum L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 69 publications
2
16
0
Order By: Relevance
“…They had high Nei genetic identity index (>0.95) and each pair clustered together in PCoA. This is in agreement with Rousselle et al (2011) who observed no loss of within population diversity and little genetic divergence of sub-populations in wheat populations cultivated over 12 generations. We found that in bi-parental subpopulations there were more alleles at most loci than in the parental varieties.…”
Section: Discussionsupporting
confidence: 75%
“…They had high Nei genetic identity index (>0.95) and each pair clustered together in PCoA. This is in agreement with Rousselle et al (2011) who observed no loss of within population diversity and little genetic divergence of sub-populations in wheat populations cultivated over 12 generations. We found that in bi-parental subpopulations there were more alleles at most loci than in the parental varieties.…”
Section: Discussionsupporting
confidence: 75%
“…Often, experiments in benign environments may not be as effective as those in natural environments in revealing the expression of dominance in fitness traits, although this is not always the case (Dudash 1990;Keller and Waller 2002;Johansen-Morris and Latta 2006). In addition, it is also possible that the divergence between populations of L. uniflora may truthfully be very shallow, so that there has not been sufficient time for the substitution of deleterious mutations in each lineage (Rouselle et al 2011). It is likely that the divergence between populations east and west of the Mississippi river is indeed very recent, since there is very little segregating variation among populations in the western portion of the species range.…”
Section: Analyses Of Line Crossesmentioning
confidence: 91%
“…Line-cross analyses involving closely related populations or ecotypes of highly selfing plants have yielded inconsistent support for the action of mutation accumulation. Crosses among highly selfing populations have sometimes shown little evidence of heterosis (Rouselle et al 2011) yet more frequently document its importance (Weller et al 2005;Johansen-Morris and Latta 2006;Hereford 2009). Observations of heterosis in these highly selfing lineages reinforce the more general finding of heterosis in many plant species with small populations and spatial structure (Ouborg and van Treunen 1994;Richards 2000;Paland and Schmid 2003).…”
Section: Analyses Of Line Crossesmentioning
confidence: 97%
“…The average inbreeding level of just the field-collected samples, which had larger sample sizes, was very similar to the full dataset (field collected F IS = 0.869, all populations F IS = 0.813). This level of inbreeding in C. benitensis is indicative of predominantly self-pollinating species like Arabidopsis thaliana (F IS = 0.92-1.0; Stenoien et al 2005), Mimulus laciniatus (F IS = 0.80; Awadalla and Ritland 1997), Medicago lupulina (F IS = 0.92; Yan et al 2009), and Triticum aestivum (F IS = 0.84-0.98; Rousselle et al 2011). It is unclear why C. contorta and C. strigulosa would have much lower levels of inbreeding.…”
Section: Within Population Inbreeding Levelsmentioning
confidence: 99%